Nitrogen doped epitaxial graphene on 4H-SiC(0001) – Experimental and theoretical study. (November 2015) - Dabrowski, P.; Rogala, M.; Wlasny, I.; Klusek, Z.; Kopciuszynski, M.; Jalochowski, M.; Strupinski, W.; Baranowski, J.M.
Abstract: The experimental and theoretical investigations of morphological and electronic properties of nitrogen-doped epitaxial graphene grown by chemical vapor deposition on 4H-SiC(0001) are discussed. It is shown that presence of nitrogen significantly affects the graphene growth process and leads to an increase in the concentration of defects (in the form of holes). Macro- and nanoscale investigations confirm the formation of pyridinic-N, pyrrolic-N and graphitic-N configurations within graphene layers. The relative concentrations of these configurations change as a function of global nitrogen concentration. Additionally, it is reported that the incorporated nitrogen results in inhomogeneous doping and a few nanometers wide spatial modification of the local density of states. Finally, the SiC substrate is also modified during the nitrogen doping process. To quantify the impact of the substrate modification on electronic structure of graphene the non-intercalated and hydrogen-intercalated doped graphene layers are compared. The presented complementary study sheds light on properties of N-doped graphene and its dependence on nitrogen concentration.